PENGARUH PENERAPAN KNOWLEDGE MANAGEMENT TERHADAP INOVASI DI PT PERTAMINA PERSERO STUDI PT PERTAMINA PERSERO UNIT PENGOLAHAN IV CILACAP - , MUHAMMAD RIZAL SYAHIIRUL ALIM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Knowledge nowadays is one of the most valuable asset that owned by a company, because knowledge has important role regarding to companyâs ability creating innovations. The rapid changing of business environment and tight competition required companies to keep innovating. This research intended to test the influence of knowledge acqusition and knowledge assimilation toward organisasional knowledge, this research also intended to see the influence of knowlege transformation, knowledge exploitation, and organisasional knowledge toward innovations success. Data for this research were collected using questionnaire from 156 respondents who are the employees of PT Pertamina Persero.The result showed that knowledge acquisition and knowledge assimilation are important factors to increase companyâs organisasional knowledge, which influenced companyâs innovation success. This research also proved that knowledge transformation and knowledge exploitation will lead companies into innovation success.